Constitutional Protection of Minorities rights in Sindh: Investigating the role of Members of Provisional Assembly-MPAs - Charan, Faisal; Keerio, Tarique Hussain; Rasool, Ghulam; Kokeyeva, Dariga; Kanyika, Martin (Pakistan Journal of Humanities and Social Sciences, 2024)
This research paper highlights the pivotal role played by the (Sindh Assembly Members SAM) in safeguarding the constitutional and basic rights of scheduled caste communities particularly of Sindh. The main goal of the presented study spins around developing a sweeping understanding of the constitutional rights outstretched to minority communities by the Sindh Assembly. The study aims at eliciting nuanced insights into the challenges faced and efforts undertaken by the Sindh Assembly concerning the constitutional rights of minority communities. The study is based on several key objectives. Firstly, it seeks to meticulously analyze the extent of the Sindh Assembly's contribution to upholding and defending the constitutional rights of minority communities. Secondly, it scrutinizes the socioeconomic status of minority groups within Sindh, shedding light on their circumstances and challenges. Additionally, the research examines the underlying reasons for the migration of minority communities from Sindh to India. Moreover, a particular focus lies in comprehending the ramifications of Hindu migration on the demographic landscape of Sindh. Moreover, the study underscores the imperative of implementing these laws and educational initiatives at the grassroots level, extending beyond urban centers to rural areas in Sindh. There is a dearth of awareness among the masses, particularly among Scheduled Castes, underscoring the necessity for widespread dissemination and implementation of these initiatives. Subsequently, the consequences of the research investigation hover to generate a trajectory for subsequent inquiries. They present an avenue to introduce novel avenues for burgeoning scholars, adept researchers, and specialists in global diplomacy.